2011
DOI: 10.1002/jsfa.4745
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physicochemical characteristics and consumer perception of rice samples with different countries of origin and prices

Abstract: Further efforts to increase the quality of rice are recommended for survival in the global market after liberalization of rice, even though consumers showed loyalty for PI of domestic samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Therefore, it can be inferred that the ethnocentrism played a key role in increasing the PI of the bread made by domestic wheat flour. Similar results with the findings of this study were also reported by Jang et al (2012) that the PI for domestic rice samples was higher in an informed test than in a blind test. In addition, the OA for highly accepted samples (JK_1, NS, and HRW_1) showed their OA increased significantly (P < 0.05) for JK_1 and NS.…”
Section: Consumer Testing Of Breadssupporting
confidence: 93%
See 4 more Smart Citations
“…Therefore, it can be inferred that the ethnocentrism played a key role in increasing the PI of the bread made by domestic wheat flour. Similar results with the findings of this study were also reported by Jang et al (2012) that the PI for domestic rice samples was higher in an informed test than in a blind test. In addition, the OA for highly accepted samples (JK_1, NS, and HRW_1) showed their OA increased significantly (P < 0.05) for JK_1 and NS.…”
Section: Consumer Testing Of Breadssupporting
confidence: 93%
“…Only NS was significantly increased by the informed test (P<0.05). Low variations between the blind and informed tests for the imported wheat might be explained by the consumers' indifference about the imported wheat since most (> 98%) of the wheat in Korea is imported in comparison with the opposite case of the rice (Jang et al, 2012).…”
Section: Consumer Testing Of Breadsmentioning
confidence: 99%
See 3 more Smart Citations